The effect of the ARIAS learning model assisted by Google Classroom media on students' critical thinking skills in sociology subjects - Hasnawati, Nadia; Sukardi, Sukardi; Nursaptini, Nursaptini (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2023)
This study aims to determine whether or not the influence of the Assurance Relevance Interest Assessment Satisfaction (ARIAS) learning model on students' critical thinking skills in sociology subjects. This study uses a quasi-experimental design type pretest-posttest control group design approach with a population of all XI social studies classes and sampling techniques in this study using random sampling techniques, namely XI social studies class 1 as a control class and XI social studies class 2 as an experimental class with the same number of students, each totaling 20 people. The instrument in this study is a multiple-choice question test that has met the quality requirements of the instrument. The data analysis used in this research is descriptive statistics and a t-test of two independent samples test, with the results showing that there is an effect of the ARIAS (Assurance Relevance Interest Assessment Satisfaction) learning model assisted by Google Classroom media on students' critical thinking skills in sociology subjects with an average score in the control class (XI IPS 1) 72.15 and the experimental class (XI IPS 2) 80. The results of the average value of the experimental class showed greater than the control class, so the ARIAS learning model assisted by Google Classroom media affects students' critical thinking skills.